Pengaruh ekstrak kulit buah naga merah (Hylocereus polyrhizus) terhadap kadar malondialdehyde (MDA) Paru pada tikus yang diberi paparan asap rokok - Raditya Pradipta; IGN Sri Wiryawan; I Wayan Sugiritama (DiscoverSys Inc., 2019)
Background: Peel of a red dragon fruit (Hylocereus Polyrhizus) is rarely utilized which is usually just thrown way, even though it contains such high antioxidants such as phenols, flavonoids and also anthocyanins.Methods: This study aims to determine the effect of red dragon fruit skin extract (Hylocereus Polyrhizus) on MDA levels of lung in rats exposed to cigarette smoke. This research is an experimental study with Post-Test Only Control Group Design. The sample consisted of 30 rats aged 2-3 months which were divided into 5 groups each amounting to 6 rats, namely 1 negative control group was not given exposure to cigarette smoke, 1 group of positive cock was exposed to cigarette smoke, 3 treatment groups were given exposure cigarette smoke and administration of red dragon fruit skin extract with doses of 20mg, 40mh and 80mg for 14 days. The parameters measured were MDA levels of the lung.Results: The mean MDA level of lung control group 1 was 0.146 ± 0.02 nmol / ml, the mean of control group 2 was 0.166 ± 0.01 nmol / ml, the mean of treatment group 1 was 0.168 ± 0.03 nmol / ml, treatment group 2 was 0.153 ± 0.02 nmol / ml, and treatment group 3 was 0.776 ± 0.09 nmol / ml. The significance analysis with the One Way Anova test shows that the value of F = 1.34 and the value of p = 0.282, where the value of p> 0.05Conclusion: There was no significant difference between the control group and the treatment group or between treatment group 1, treatment 2 and treatment 3. Latar Belakang: Kulit buah naga merah (Hylocereus Polyrhizus) merupakan limbah yang sangat jarang dimanfaatkan, biasanya kulit buah naga merah hanya dibuang begitu saja, padalah mengandung antioksidan yang begitu tinggi seperti fenol, flavonoid dan juga antiosianin.Metode: Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak kulit buah naga merah (Hylocereus Polyrhizus) terhadap kadar MDA paru pada tikus yang dipaparkan asap rokok. Penelitian ini merupakan penelitian eksperimental dengan Post-Test Only Control Group Design. Sampel terdiri dari 30 ekor tikus yang berumur 2-3 bulan yang dibagi menjadi 5 kelompok masing-masing berjumlah 6 ekor tikus, yaitu 1 kelompok kontrol negative tidak diberikan paparan asap rokok, 1 kelompok kontrol positif diberikan paparan asap rokok, 3 kelompok perlakuan diberikan paparan asap rokok dan pemberian ekstrak kulit buah naga merah dengan dosis 20mg, 40mg dan 80mg selama 14 hari. Parameter yang diukur adalah kadar MDA paru.Hasil: Rerata kadar MDA paru kelompok kontrol 1 adalah 0,146 ± 0,02 nmol/ml, rerata kelompok kontrol 2 adalah 0,166 ± 0,01 nmol/ml, rerata kelompok perlakuan 1 adalah 0,168 ± 0,03 nmol/ml, kelompok perlakuan 2 adalah 0,153 ± 0,02 nmol/ml, dan kelompok perlakuan 3 adalah 0,776 ± 0,09 nmol/ml. Analisis kemaknaan dengan uji One Way Anova menunjukan bahwa nilai F= 1,34 dan nilai p= 0,282, dimana nilai p>0,05Simpulan: Tidak ada perbedaan yang bermakna antara kelompok kontrol dengan kelompok perlakuan maupun antara kelompok perlakuan 1, perlakuan 2 dan perlakuan 3.